Toll-like Receptor (TLR)-induced Rasgef1b expression in macrophages is regulated by NF-κB through its proximal promoter. (October 2020) - Leão, Felipe B.; Vaughn, Lauren S.; Bhatt, Dev; Liao, Will; Maloney, Dillon; Carvalho, Brener C.; Oliveira, Leonardo; Ghosh, Sankar; Silva, Aristóbolo M.
Highlights: Immune response-related elements are present in the 5′ flanking sequence of Rasgef1b . Minimal TLR-responsive promoter region harbors Sp1 and NF-κB binding sites. Rasgef1b promoter is located in an accessible chromatin region. NF-κB RelA is recruited to Rasgef1b promoter upon LPS stimulation of macrophages. Optimal TLR-induced expression of Rasgef1b requires NF-κB. Abstract: Ras Guanine Exchange Factor (RasGEF) domain family member 1b is encoded by a Toll-like receptor (TLR)-inducible gene expressed in macrophages, but transcriptional mechanisms that govern its expression are still unknown. Here, we have functionally characterized the 5′ flanking Rasgef1b sequence and analyzed its transcriptional activation. We have identified that the inflammation-responsive promoter is contained within a short sequence (-183 to +119) surrounding the transcriptional start site. The promoter sequence is evolutionarily conserved and harbors a cluster of five NF-κB binding sites. Luciferase reporter gene assay showed that the promoter is responsive to TLR activation and RelA or cRel, but not RelB, transcription factors. Besides, site-directed mutagenesis showed that the κB binding sites are required for maximal promoter activation induced by LPS. Analysis by Assay for Transposase-Accessible Chromatin using sequencing (ATAC-seq) revealed that the promoter is located in an accessible chromatin region. More important, Chromatin Immunoprecipitation sequencing (ChIP-seq) showed that RelA is recruited to the promoter region upon LPS stimulation of bone marrow-derived macrophages. Finally, studies with Rela -deficient macrophages or pharmacological inhibition by Bay11-7082 showed that NF-κB is required for optimal Rasgef1b expression induced by TLR agonists. Our data provide evidence of the regulatory mechanism mediated by NF-κB that facilitates Rasgef1b expression after TLR activation in macrophages.